Cognitive development in babies with exclusive breastfeeding using Mullen Scale test - I G. Maharditha; Soetjiningsih Soetjiningsih; I K. G. Suandi (Paediatrica Indonesiana, 2008)
Background Breast milk is the best nutrition for babies' growthand development. There are many reasons for discontinuation ofexclusive breastfeeding (BF).Objective To evaluate the impact of exclusive breastfeeding onbabies' cognitive development.Methods A cohort study was conducted for full term newbornbabies. They were evaluated for cognitive development usingMullen scale test at of 6 and 9 months; t test was used to obtainmean difference of cognitive values. Logistic regression analysiswas performed to distinguish factors associated with the cognitivedevelopment.Results One hundred and forty babies were enrolled to this study(70 babies with exclusive BF and 70 babies with non-exclusiveBF). There were 34 boys (49%) in exclusive and 37 boys (53%) innon-exclusive BF group. Mean cognitive score at age six monthswas 1.41 points higher for exclusive BF group, mean rate 174.31(SO 4.89) and 172.90 (SO 4.19) for exclusive and non-exclusive BF,respectively. Mean cognitive score at nine months was 1.49 pointhigher in exclusive BF group with mean rate 175.28 (SO 4.39) and173.82 (SO 3.80) for exclusive and non-exclusive BF respectively.Logistic regression analysis showed that exclusively breastfed babieshad higher mean Mullen cognitive score of 4. 761 (95% CI 1.341;16.907) and 4.431 (95% CI 1.313; 14.949) times at sixth and ninthmonth respectively than non-exclusive BEConclusion Exclusively breastfed babies may have higher meanscore of Mullen cognitive score at sixth and ninth months whencompared with those who are non exclusively breastfed.